2017
DOI: 10.1007/s11695-017-2873-5
|View full text |Cite
|
Sign up to set email alerts
|

Five Years, Two Surgeons, and over 500 Bariatric Procedures: What Have We Learned?

Abstract: The surgeons involved in this project have built a busy bariatric surgery practice, while continually evolving the postoperative algorithm. Nearly every aspect of postoperative care has been deescalated while decreasing length of stay and cost to the hospital. All of this has been obtained without incurring any increase in complications, re-operations, or re-admissions. The authors of this paper hope to use this article as a launching point for a formal advanced recovery pathway for bariatric surgery at their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…At present, similar comparison studies between LGB and LSG showed postoperative response rates were above 80% for both procedures (30,31). In our study, the relative low remission rate may be a result of the use of the remission criteria of ADA.…”
Section: Discussionsupporting
confidence: 65%
“…At present, similar comparison studies between LGB and LSG showed postoperative response rates were above 80% for both procedures (30,31). In our study, the relative low remission rate may be a result of the use of the remission criteria of ADA.…”
Section: Discussionsupporting
confidence: 65%
“…Several bariatric ERAS studies, including one randomized trial [ 3 ] and three meta-analyses [ 4 6 ], have reported patient safety equivalent to standard postoperative protocols while achieving more rapid mobilization, briefer lengths of stay (LOS), decreased costs, and a faster return to normal activities [ 1 , 7 10 ]. Recent bariatric ERAS and fast-track studies report that anticoagulants are often administered prophylactically to all bariatric patients, and in higher doses to those with a body mass index (BMI) ≥ 40 kg/m 2 [ 11 – 14 ]. The all-inclusive approach was confirmed as the norm in a 2017 systematic review and guideline published by the European Venous Thromboembolism Prophylaxis Task Force, in which a paucity of high-quality randomized controlled trials precluded their providing strong, specific thrombophylaxis recommendations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%